Determinants of Cash Waqf Intention on Female Muslim at Brunei and Indonesia - Adib Susilo; Nurdianawati Irwani Abdullah; Nor Azizan Che Embi (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 10 Issue 2 Page (14–27)